2020
DOI: 10.3390/genes11080925
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spectrum of BRCA Germline Variants in Central Italian High Risk or Familial Breast/Ovarian Cancer Patients: A Monocentric Study

Abstract: Hereditary breast and ovarian cancers are mainly linked to variants in BRCA1/2 genes. Recently, data has shown that identification of BRCA variants has an immediate impact not only in cancer prevention but also in targeted therapeutic approaches. This prospective observational study characterized the overall germline BRCA variant and variant of uncertain significance (VUS) frequency and spectrum in individuals affected by breast (BC) or ovarian cancer (OC) and in healthy individuals at risk by sequencing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
(41 reference statements)
1
10
3
2
Order By: Relevance
“…The percentage of BRCA1 PVs found in our study was higher than that of the BRCA2 PVs (68.4% and 31.6, respectively). This distribution differs from that of other Italian regions [ 21 , 22 , 23 ] where the percentage of PVs observed in the 2 genes is generally the same, except for Sardinia where BRCA2 PVs are more frequent [ 26 ].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The percentage of BRCA1 PVs found in our study was higher than that of the BRCA2 PVs (68.4% and 31.6, respectively). This distribution differs from that of other Italian regions [ 21 , 22 , 23 ] where the percentage of PVs observed in the 2 genes is generally the same, except for Sardinia where BRCA2 PVs are more frequent [ 26 ].…”
Section: Discussioncontrasting
confidence: 57%
“…A pathogenic variant was identified in 24.5% probands. This figure is higher than the prevalence reported in other Italian regions: 10% in Sardinia [ 26 ], 14.8% in Sicily [ 21 ], 13.8% in Central Italy [ 22 ], and 18.9% in northeastern Italy [ 23 ]. While interesting, this finding is severely limited by the different genetic test access criteria used in the previous reports.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, they indicate that:1./ This is additional evidence suggesting that the controversial CHEK2 variant c.599T>C (p.Ile200Thr) represents with high probability a low penetrance variant associated with lower susceptibility of cancer risk[62] mainly because it is known that CHEK2 protein affected by this missense variant has a lower activity[65].2./ The presence of pathogenic mutations in HBOC-associated genes relates to the notable decrease of the age of cancer diagnosis and this fact results in a significant increase of mutation frequency with decreasing age at diagnosis[69].Overall, the age at cancer diagnosis in our study is relatively low when comparing with other multigene based studies. For example, Foglietta et al[47] reported the mean age in the group of breast cancer cases to be 46 years and in the BRCA1/2 positive cases even higher at 48 years, while the mean age in our group of breast cancer patients was 43.7 and in positive cases at 43.5. Similar average age of breast cancer cases at 43.2 years was reported also in their study by Felicio et al[70].…”
mentioning
confidence: 44%
“…In the French HBOC population, Velásquez et al[45] and Benusiglio et al[46] detected 8.3% and 12.1% in the group of 128 and 234 cases, respectively. Foglietta et al[47] reported a mutation detection rate of 13.8% in the group of 363 cases in the Italian population and Lerner-Ellis et al[40] detected a mutation detection rate at a level of 9.1% in 3,251 cases in the population of Ontario. Such discrepancies in the identified PV/LPV frequencies between the various studies may be explained by the number and composition of analysed samples and differences in the indication criteria between several countries.…”
mentioning
confidence: 99%